Socioeconomic status: A theoretical framework for the development and use of assessment tools - Pradeep R Deshmukh; Sujiv Akkilagunta (Wolters Kluwer Medknow Publications, 2020)
Decades of research have established the relationship between socioeconomic status (SES) and health. The tools for the assessment of SES have evolved ever since, growing in complexity over time. The purpose of measuring SES in health research is twofold - to causally link the exposure to poor SES with health state and to find out the causal mechanisms to devise programmatic interventions. In health research, SES should be viewed as a determinant of unequal distribution of health resources that further leads to health disparities. We refer to socioeconomic position as an umbrella term for social stratification that defines individuals/households based on the present circumstances. Socioeconomic position can be measured in three distinctly varied ways - socioeconomic disadvantage, social class, and SES (or position). Tools for the measurement of SES can be classified as indices based on income and expenditure, indices bases on occupation and education, wealth index combining education, and asset-based wealth index. Each tool has its own theoretical assumptions - Weberian, Marxist, or Functionalist perspectives. The choice of tool should depend on theoretical assumptions. The tool should be comprehensive, including all three dimensions - education, occupation, and income. Life-course perspective, linking the timing of exposure to poor SES over the life course is useful in the development of interventions. Study tools incorporating a life course perspective in the measurement of SES are the need of the hour.